Brain Connectivity During Walking and Obstacle Avoidance in Persons With Multiple Sclerosis and Healthy Controls: A Pilot EEG Study - Al-Shargie, Fares; Glassen, Michael; DeLuca, John; Saleh, Soha (IEEE transactions on neural systems and rehabilitation engineering, 2025)
This study investigated effective connectivity and hemispheric asymmetry in persons with multiple sclerosis (pwMS) compared to healthy controls (HC) during two walking conditions: walking alone and walking while avoiding unpredictable obstacles. Cognitive-motor interference (CMI) was analyzed using electroencephalography (EEG) across beta, alpha, and theta frequency bands. Directed functional connectivity was estimated using partial directed coherence (PDC) to assess differences in connectivity patterns between conditions and groups. In healthy controls, obstacle avoidance increased connectivity in motor and cognitive regions including left central (LC), left temporal (LT), and right frontal (RF) regions, p<0.0014. In contrast, pwMS demonstrated weaker and more localized connectivity, primarily in the left central regions (sensorimotor cortices) p<0.0013, suggesting reduced efficiency in brain networks and compensatory mechanisms to maintain task performance. Further, pwMS showed left laterality toward the central region during both walking conditions compared to HC, p<0.05. Correlational analysis revealed that connectivity during obstacle avoidance in HC positively correlated with comfortable walking speed (r =0.57), indicating efficient neural pathways. In pwMS, connectivity showed a negative correlation with walking speed (r = -0.65 ), indicating compensatory but inefficient neural engagement. These findings highlight disruptions in brain connectivity during motor-cognitive tasks in pwMS, with potential implications for designing targeted rehabilitation strategies to improve gait and neural efficiency.